Factors Associated with Postpartum Family Planning in a Cohort of Kelantanese Women with Previous Caesarean Delivery in Malaysia - I, Hafizah; TI, Tengku Alina; MH, Suhaily; S, Zaharah (IIUM Medical Journal Malaysia, 2020)
Introduction: This community-based, cross-sectional study aimed to identify the factors associated with postpartum family planning use among a cohort of women with recent caesarean delivery in a state with the lowest contraceptive use in Malaysia. Materials and Methods: A total of 281 women aged between 18-49 years old who had caesarean delivery in government tertiary centres in Kelantan from January until April 2017 were enrolled in this study. The study was conducted from January until April 2018. Women were selected through stratified random sampling with probability proportional to size. Data were collected through a validated structured questionnaire. The main outcome was binary (postpartum family planning use or non-use). The factors included socio-demographic details, reproductive history, previous contraceptive use, contraceptive health education received, knowledge, and social support. Simple and multiple logistic regression were conducted to identify significant determinants of postpartum family planning use. Results: The factors associated with postpartum family planning use included a secondary and below education level of women (AOR= 2.37, 95% CI (1.05, 5.34)), previous contraceptive use (AOR= 9.82, 95% CI (4.81, 20.06)), individual health education (AOR= 4.19, 95% CI (1.23, 14.30)), higher knowledge score (AOR= 1.12, 95% CI (1.03, 1.23)), and higher social support score (AOR= 1.09, 95% CI (1.03, 1.16)). Conclusions: here remains a need to enhance personalised contraceptive counselling in the primary care setting as well as to promote longer acting reversible contraceptive methods.